2005
DOI: 10.1586/14760584.4.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as carriers for nasal vaccine delivery

Abstract: At present, there is considerable excitement within the nanotechnology field with regard to the potential use of nanosystems as carriers for mucosal vaccine delivery. Indeed, many of the vaccines available, including protein antigens and DNA vaccines, are very unstable and need to be protected from degradation in the biologic environment. In addition, their efficacy is limited by their poor capacity to cross biologic barriers and reach the target sites. As a consequence, the design of appropriate antigen carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(54 citation statements)
references
References 61 publications
0
54
0
Order By: Relevance
“…SDS-PAGE analysis and relative potency studies indicated that the structure of the incorporated antigen remained intact upon formulation. The particle size has been described to possess effect on the immune adjuvant properties of the vaccine carriers (Köping-Höggård et al, 2005;Vila et al, 2005). The CS and GC NPs were of similar size, i.e., approximately 200 nm.…”
Section: Discussionmentioning
confidence: 99%
“…SDS-PAGE analysis and relative potency studies indicated that the structure of the incorporated antigen remained intact upon formulation. The particle size has been described to possess effect on the immune adjuvant properties of the vaccine carriers (Köping-Höggård et al, 2005;Vila et al, 2005). The CS and GC NPs were of similar size, i.e., approximately 200 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of antigens and adjuvants into nanoparticles and nanoemulsions is another way of increasing immune responses, as they can be taken up by antigen-presenting cells, even on a mucosal surface (63,89,100).…”
Section: Adjuvantsmentioning
confidence: 99%
“…The accomplishment of these objectives would improve vaccination coverage for several infectious diseases, especially in developing countries. Although the mucus vaccine delivery strategy is regarded as a potent needle-free vaccine delivery method, the limitations associated with the mucociliary clearance mechanism inhibit the delivery of Ags to the immune system (58). Accordingly, new approaches for mucus vaccine delivery systems that can improve Ag passage through biological barriers, such as the intestinal and nasal mucosa, are in high demand.…”
Section: Discussionmentioning
confidence: 99%